Reducing the computational time of the SPH method with a coupled 2-D/3-D approach - Džebo, Elvira (Strojniški vestnik, 2013)
Smoothed particle hydrodynamics (SPH) is a particle-based Lagrangian method that can be adapted for simulating free surface flows. Themethod is particularly suitable for phenomena in which the flow changes rapidly. A weakness of the SPH method is the very long computationaltime. However, this can be significantly reduced using new techniques. In this research, the two-dimensional (2-D) and three-dimensional (3-D) models Tis Isat, developed at the University of Ljubljana, were used with an appropriate coupling procedure. The new model was validatedand calibrated against the results of laboratory experiments. The simulation results of the 2-D/3-D coupled model were compared to themeasurements, to the results of the fully 3-D Tis Isat model and to the results of a one-dimensional (1-D) finite difference (FD) model. Theperformed SPH simulations showed good agreement with measurements and the 1-D model results in the symmetry axis of the channel. Thetwo greatest advantages of the coupled model are a more realistic description of the water-level below the expansion and the significantlyshorter computational time as a result of the adopted coupling procedure.
Keywords: 2-D coupling; 2-D povezovanje modela; 3-D coupling; 3-D povezovanje modela; free-surface flow; hidrodinamika zglajenih delcev; smoothed particle hydrodynamics; SPH metoda; tok s prosto gladino